Kamala, Mammadova - (:unkn) unknown (My University, 2026)
Kamala Mehdi Mammadova enrolled in the Faculty of Economics and Management in Construction at the Azerbaijan Institute of Civil Engineers in 1990 and graduated with honors in 1995, earning a degree in Engineering Economics. She began her professional career in 1995 as a Senior Laboratory Assistant at the Department of Economics of the Azerbaijan University of Architecture and Construction. In 2003, she was appointed Lecturer at the Department of Business Economics and Management and subsequently promoted to Senior Lecturer. In 2017, she was awarded the degree of Doctor of Philosophy (PhD) in Economics in the field of 5312.01 – Sectoral Economics. Since 2021, she has been an Associate Professor at the Department of Business Economics and Management of the Azerbaijan University of Architecture and Construction. Dr. Mammadova has extensive academic and research experience in economics, strategic management, leadership, and sectoral economics. She is the author of nearly 100 scientific publications, 35 educational curricula, and the textbook *Strategic Management and Leadership*, intended for higher education institutions.